The effects of various flame retardants on the combustion of polypropylene: Combining optical diagnostics and pyrolysis fragment analysis. (May 2023) - Geschwindner, Christopher; Goedderz, Daniela; Li, Tao; Bender, Johannes; Böhm, Benjamin; Dreizler, Andreas
Highlights: Interdisciplinary methodical approach to assess the mode of action of flame retardants in polypropylene. Four different flame retardant additives with varying retardation effects are experimentally investigated. Thermogravimetric analysis coupled to Fourier-transform infrared spectroscopy provides knowledge on the thermal decomposition products. Laser-induced fluorescence of the OH radical visualizes the combustion of micrometer-sized particles and stick-shaped specimens in custom-built test environments. The methodical combination provides a comprehensive knowledge on polymer chemistry and combustion dynamics for the selected flame retardants in polypropylene. Abstract: The assessment of the efficacy and mode of action of flame retardants in polymers requires a thorough knowledge of the coupling of the presence of chemical inhibitors with the underlying heat and mass transport processes. In this experimental work, we combine a thermal decomposition analysis with optical combustion diagnostics in different test environments to gain a comprehensive understanding of the relevant sub-processes and demonstrate how this approach provides future opportunities for the research regarding the mode of action of flame retardants. Four different composites of polypropylene (PP) and 10 wt% of selected flame retardants as well as neat PP are prepared. Flame retardants include pentaerythritol spirobis(methylphosphonate) (PSMP), zinc diethylphosphinate (DEPZn), aluminum hydroxide (i.e. aluminum trihydrate, ATH) and ammonium polyphosphate (APP). The released substances in the gas phase are investigated by using thermogravimetric analysis coupled to Fourier-transform infrared spectroscopy (TGA-FTIR), and the burning behavior regarding carbon monoxide concentration and heat release rate (HRR) is studied in cone calorimeter experiments. The ignition and combustion of flame retarded micrometer-sized particles of PP are experimentally investigated in a laminar flat flame burner by means of simultaneous scanning planar laser-induced fluorescence of OH radicals (OH-PLIF) and diffuse back-illumination (DBI) at a repetition rate of 10 kHz. Particles with gas-phase activity show a decreased normalized OH signal intensity during combustion. A dependency of the dimensionless flame radius on the particle size is found which can be linked to the faster heating and pyrolysis of smaller particles compared to large particles and agglomerations. Eventually, the interaction with an external premixed flame and the subsequent extinction of self-sustaining flames of polymer sticks is investigated using OH-PLIF in an adapted horizontal burning test suited for the application of optical diagnostics. This approach allows to link the findings of investigations encompassing multiple scales, resulting in a thorough understanding of both polymer chemistry and combustion dynamics in flame retarded polymers.